Pacemaker‐induced ventricular fibrillation during radiofrequency catheter ablation for ventricular tachycardia. Issue 2 (14th February 2021) - Nam, Michael C. Y.; Jones, Nikki; Claridge, Simon; Balasubramaniam, Richard; Sopher, Mark; Babu, Girish
Abstract : Prior to ventricular tachycardia ablation, this patient's cardiac implantable electronic device (CIED) was temporarily programmed to backup pacing mode with tachycardia therapies disabled. During radiofrequency energy delivery, the patient developed ventricular fibrillation requiring emergent cardioversion. Electrogram interrogation showed that the CIED switched to noise reversion mode during ablation. The consequent asynchronous pacing resulted in a paced QRS landing on an intrinsic T wave, inducing ventricular fibrillation. This serves as an important reminder that asynchronous pacing consequent to CIED oversensing could occur in any procedure that could cause electromagnetic interference such as radiofrequency cathteter ablation.